Long-term analysis on the variance of extra-group paternities in rhesus macaques - Ruiz-Lambides, Angelina V. (Behav Ecol Sociobiol, 2017)
ABSTRACT: Extra-group paternity (EGP) has been described in various mammalian species; however, little is known about which factors contribute to the variation in EGP, as the majority of studies were restricted in time and the number of groups considered. Using longitudinal demographic and genetic data, we aim to investigate which factors predict rates of EGP in the free-ranging rhesus macaque population of Cayo Santiago, Puerto Rico (USA). Of the 1649 infants considered which were born into six social groups over 9 years, we identified an average of 16% of infants resulting from EGPs. We tested the influence of group size, breeding group sex ratio, female reproductive synchrony, and group instability on the occurrence of EGPs. Our results suggest a tendency for EGPs to increase as the proportion of females increased in larger groups, but no such effect in smaller groups. Furthermore, as group instability and female reproductive synchrony decreased, the number of EGPs tended to increase. Our results support the hypothesis that group structure affects the occurrence of EGPs, which might be mediated by male mating opportunities, male monopolization potential, and/or female choice. SIGNIFICANCE STATEMENT: In several species, both sexes seek alternative reproductive strategies to enhance their reproductive success. For instance, females may pursue EGPs to potentially increase genetic compatibility with males, or males may seek EGPs to improve their mating opportunities. Our longitudinal analysis, including demographic and genetic data over 9 years of six social groups of rhesus macaques, revealed high variation in the occurrence of EGPs across groups and years, and this variation tended to depend on group characteristics such as breeding group size, sex ratio, female synchrony, and group instability. The data suggest that group structure affects the number of EGPs in this group-living primate. Our results show that EGPs can affect the distribution of paternity within social groups and should be taken into account when assessing reproductive success. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00265-017-2291-7) contains supplementary material, which is available to authorized users.